Mediating effect of illness perception between self-care ability and health-promoting behaviors among patients with stable coronary artery disease. - Yuanyuan Wang; Xinyue Gong; Jing Cheng; Yingting Wu; Sihan Wang; Ying Zhu; Changyi Liu; Fei He; Kehui Xu (PLoS ONE)
Background The interaction between illness perception, self-care ability, and health-promoting behaviors (HPB) in stable coronary artery disease (SCAD) patients remains uncertain. We conducted a cross-sectional survey to explore the correlation between self-care ability, illness perception, and HPB among patients with SCAD, as well as the potential mediating role of illness perception between self-care ability and HPB. Methods A cross-sectional study was carried out among 184 inpatients with SCAD in Hefei, China, from December 2022 to March 2023. The Self-Care of Coronary Heart Disease Inventory (SC-CHDI, containing three dimensions: self-care maintenance, self-care management, and self-care confidence), Revised Illness Perception Questionnaire (IPQ-R, containing seven dimensions: illness duration, illness consequence, personal control, treatment control, illness coherence, cyclical timeline, emotional distress), Health-Promoting Lifestyle Profile Ⅱ (HPLP-Ⅱ) were used in the questionnaires. SPSS 25.0 software and PROCESS version 4.2 plug-in was used to analyze the mediating effect. Results HPB of SCAD patients was at moderate level. A range of factors including education level, marital status, self-care maintenance, self-care management, self-care confidence, illness coherence, and emotional distress are potential influencers of HPB. Illness coherence had a partially mediated effect between self-care maintenance and HPB (β = 0.063, 95% CI: 0.021~0.111), accounting for 20.59% of the total effect. Similarly, illness coherence had a partially mediated effect between self-care management and HPB (β = 0.055, 95% CI: 0.016~0.105), accounting for 13.78% of the total effect. However, none of the dimensions of illness perception mediated between self-care confidence and HPB. Self-care confidence directly influenced HPB, accounting for 92.40% of the total effect. Conclusion It is necessary for hospital healthcare workers, community workers, and patients' families to work together to focus on the self-care ability and positive illness perception of patients with cardiovascular disease, so as to increase patients' motivation to participate in HPB and improve their quality of life.